2006
DOI: 10.1116/1.2201054
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot nanodevices with carbon nanotubes

Abstract: Articles you may be interested inPerfect spin-filter and quantum-signal generator in a parallel coupled multiple triple-quantum-dots deviceWe review our recent work on quantum-dot devices with carbon nanotubes. We conclude that the single-wall carbon nanotube quantum dot is an artificial atom with two-or four-electron shell structures. Zeeman splitting of single particle levels was observed, which is advantageous for the spin based quantum computing device ͑spin qubit͒ because the single spin is generated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…1,2 Compared with other self-assembled one-dimensional materials, e.g., carbon nanotubes, 3 SiNWs allow us to use matured Si fabrication processes, which enhances reliability and reproducibility of the fabricated devices. These SiNWs with the diameters that are difficult to realize with conventional lithography techniques could be attractive building blocks for extremely small quantum-dot based nanodevices and have stimulated extensive interest in the past years.…”
mentioning
confidence: 99%
“…1,2 Compared with other self-assembled one-dimensional materials, e.g., carbon nanotubes, 3 SiNWs allow us to use matured Si fabrication processes, which enhances reliability and reproducibility of the fabricated devices. These SiNWs with the diameters that are difficult to realize with conventional lithography techniques could be attractive building blocks for extremely small quantum-dot based nanodevices and have stimulated extensive interest in the past years.…”
mentioning
confidence: 99%
“…19,20,26,27 From the low temperature (4.2 K) electronic transport measurements of 50 devices, we found that the majority of the devices with R T > 100 kΩ show SET behavior. The approach is based on the integration of solution processed individual SWNTs between the pre-fabricated source and drain electrodes via DEP followed by deposition of a metal contact to create 100 nm SWNT devices.…”
Section: Introductionmentioning
confidence: 88%
“…However, most of the reported gold single electron transistors, which showed promising results such as a "high working temperature" [9]-[11], used a zero dimensional quantum dot, a nanoparticle, resulting in a difficult gate control of the charge. Thus, in order to develop a technology like carbon nanotube one charge devices [12] that show similar dimensions, the investigation of the gold nanowire electrical transport should provide valuable results given the higher atomic number of this chemical element. We present here the fabrication process and electrical characteristics of a gold based Single Electron Transistor (SET): wet synthesized ultra-thin AuNWs used as a quantum dot and connected to metal electrodes patterned with electron beam lithography.…”
Section: Introductionmentioning
confidence: 99%